2016
DOI: 10.18805/ijar.9294
|View full text |Cite
|
Sign up to set email alerts
|

Measuring technical, allocative and economic efficiencies of dairy farms in western Turkey

Abstract: A study was conducted to determine the input efficiencies of 43 dairy cattle farms under the aegis of Agricultural Development Cooperative in Erikler Village of Center Town of Kirklareli Province in Western Turkey. Data envelopment analysis was used. The technical, allocative and economical efficiencies were found to be as 0.66, 0.43 and 0.23 respectively. The analysis results showed that only 23.26% of the farms were efficient (they had constant return to scale) regarding the usage of major inputs while the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Kumbar (2015) show that TE and SE scores are 0.49 and 0.80. These scores are 0.661 and 0.759 in Kırklareli (Terin et al, 2017). Both the efficiency scores in our research are higher than in earlier studies.…”
Section: Results Of Deacontrasting
confidence: 73%
“…Kumbar (2015) show that TE and SE scores are 0.49 and 0.80. These scores are 0.661 and 0.759 in Kırklareli (Terin et al, 2017). Both the efficiency scores in our research are higher than in earlier studies.…”
Section: Results Of Deacontrasting
confidence: 73%
“…in 150 dairy farms of Turkey and using the DEA for estimating TE achieved an average of 0.80 for inefficient farms, which indicates those farms could reduce their average input by 20%. For the same country, but with 43 dairy farms,Terin et al (2017), and using DEA, found the technical, allocative and economical efficiencies as 0.66, 0.43 and 0.23, respectively. The results showed that only 23.26% of the farms were efficient (CRS).…”
mentioning
confidence: 95%
“…production efficiency was low due to quantities of inputs used were higher or lower than the required to achieve present level of output. Terin et al (2017) stated that, the lack of correct knowledge about the input uses among some producers could possibly be one of the main obstacles against the efficient input uses.…”
Section: Technical Allocative and Cost Efficiencymentioning
confidence: 99%